The correlates of physical activity among the population aged 50-70 years (Determinantes de la actividad física entre las personas de 50 a 70 años) - Lera López, Fernando; Garrues Irisarri, Mirian A.; Suárez Fernández, María José (Retos, 2017)
Background: Physical activity is of particular interest due to its potential for improving quality of life and reducing health care costs. The contribution of this paper is to analyse the correlates of physical activity (PA) among individuals aged 50-70 years old. We differentiate between physical activity during leisure time (LTPA) and total physical activity (Total PA) and besides we offer potential policy advice to increase PA. Methods: We use a cross-sectional survey from a sample of Spanish individuals between 50 and 70 years of age. We analyse the correlates of LTPA and Total PA by estimating ordered probit models including socio-demographic characteristics, health and emotional wellbeing and social support. Results: The covariates explain in different ways LTPA and Total PA levels. In particular, the accomplishment of a minimum of LTPA is positively related to partner participation in LTPA (p